Pewarisan Hak Atas Tanah Yang Dibebankan Hak - Ni Komang Evic Triani; I Ketut Sukadana; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
Land ownership is the highest land rights in any country. Property Right apart from being transferred can also be borne by mortgages or used as collateral for debt repayment.Land ownership has economic value for human needs. Apart from being transferred, Land ownership can also be borne by mortgages or pledged as collateral for repayment of debt. Land ownership can be transferred because inheritance of acquired land and inheritance is important to be registered to obtain legal certainty. The formulation of the problem raised in this study is; (1) What is the process of inheritance of land rights imposed with Mortgage Rights? and (2) What are the consequences faced by creditors for the inheritance of rights to land that are charged with Mortgage rights? This study aims to determine the process of inheritance of land rights that are charged with Mortgage Rights. This normative study with a method of approaching the problem of legislation with a conceptual approach. Based on the results of this study can be concluded that the process of transferring land rights due to inheritance occurs because of law. Heirs have to pay all debts left by the heir. The consequences faced by creditors are to wait for the process of returning the name of the object to the mortgage. A certificate issued by a land office has the same legal force as a court decision.